2020
DOI: 10.1007/s43450-020-00105-6
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacokinetic Study by LC-MS/MS to Quantify Isoquercetin and Astragalin in Rat Serum After Oral Administration of a Combined Extract of Moringa oleifera and Centella asiatica

Abstract: TGT-PRIMAAGE is a combination of leaf extracts from Moringa oleifera Lam, Moringaceae, and Centella asiatica (L.) Urb., Apiaceae. It was previously proven on its potentials to reduce oxidative stress and senescence in hydrogen peroxide-induced human dermal fibroblasts and to improve in memory and learning abilities. This mixture is rich in phenolic and flavonoids, which include astragalin and isoquercetin. The aim of this study was to develop and validate an analytical method by liquid chromatography coupled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Based on previous results, LOD and LOQ for each flavonoid were highly sensitive which suggest that this method should be useful in pharmacokinetic studies. [8,[11][12][13]. Finally, the chromatographic method showed good linearity with a correlation coefficient larger than 0.99 to each signal.…”
Section: Quality Controlmentioning
confidence: 80%
See 2 more Smart Citations
“…Based on previous results, LOD and LOQ for each flavonoid were highly sensitive which suggest that this method should be useful in pharmacokinetic studies. [8,[11][12][13]. Finally, the chromatographic method showed good linearity with a correlation coefficient larger than 0.99 to each signal.…”
Section: Quality Controlmentioning
confidence: 80%
“…The results showed that the recovery of myricitrin was between 87.48% to 97.37% with a precision of <12.82% [11]. Another study to quantify isoquercetin and astragalin reported precision between 1.4% to 10.72% and accuracy >94.78% [12].…”
Section: Quality Controlmentioning
confidence: 96%
See 1 more Smart Citation
“…The detection of rhodomyrtone as was as described by Rofiee et al, [28] Rhodomyrtone in the SERT were detected using LC-MS-QTOF. About 1 mg/mL of Rhodomyrtus tomentosa ethanolic extract were reconstituted in the mobile phase.…”
Section: Standardize Compound Of Sertmentioning
confidence: 99%